Wall teichoic acid-dependent phagocytosis of intact cell walls of Lactiplantibacillus plantarum elicits IL-12 secretion from macrophages - Kojima, Naoya; Kojima, Shohei; Hosokawa, Shin; Oda, Yoshiki; Zenke, Daisuke; Toura, Yuta; Onohara, Emi; Yokota, Shin-ichi; Nagaoka, Masato; Kuroda, Yasuhiro (Frontiers in Microbiology, 2022)
Selected lactic acid bacteria can stimulate macrophages and dendritic cells to secrete IL-12, which plays a key role in activating innate and cellular immunity. In this study, we investigated the roles of cell wall teichoic acids (WTAs) displayed on whole intact cell walls (ICWs) of Lactiplantibacillus plantarum in activation of mouse macrophages. ICWs were prepared from whole bacterial cells of several lactobacilli without physical disruption, and thus retaining the overall shapes of the bacteria. WTA-displaying ICWs of several L. plantarum strains, but not WTA-lacking ICWs of strains of other lactobacilli, elicited IL-12 secretion from mouse bone marrow-derived macrophages and mouse macrophage-like J774.1 cells. The ability of the ICWs of L. plantarum to induce IL-12 secretion was abolished by selective chemical elimination of WTAs from ICWs, but was preserved by selective removal of cell wall glycopolymers other than WTAs. In addition, IL-12 secretion by ICWs of L. plantarum occurred irrespective of TLR signaling. WTA-displaying ICWs, but not WTA-lacking ICWs, were ingested in the cells within 30 min. Treatment with cytochalasin D, an inhibitor of actin polymerization, abolished IL-12 secretion in response to ICW stimulation and diminished ingestion of ICWs. When overall shapes of ICWs of L. plantarum were physically disrupted, the disrupted ICWs (DCWs) failed to induce IL-12 secretion, although they were ingested by the cells more efficiently than ICWs via an actin-independent manner. Finally, DCWs and soluble WTAs inhibited ICW-stimulated IL-12 secretion from macrophages. Taken together, these results show that WTAs displayed on ICWs with preserved bacterial shapes are key molecules in elicitation of rapid phagocytosis of ICWs and subsequent IL-12 secretion from macrophages after stimulation with ICWs of L. plantarum.